Minang Ulamas And Religious Conversions In South Sulawesi And North Mollucas - Irwan Abbas; Darmawijaya; Mohamad Na’im (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to explain the role of Minang Malay ulama in the process of religious conversion of the rulers in South Sulawesi and in North Maluku. This study uses qualitative research using a historical method approach that begins with heuristic steps (collection of sources), verification (source criticism), both internal and external, interpretation, and ends with historiography (writing). The conclusion found that the existence of Muslims in South Sulawesi existed long before Islam was made the official religion of the Bugis Makassar kingdoms. The process of religious conversion from animism and dynamism to become a Muslim thanks to the services of three Minang Malay scholars, namely Datuk ri Tiro, Datuk ri Bandang and Datuk Patimang. The bias from interactions with the Minang Malays to this day has left its mark on the lives of the Makassarese in South Sulawesi. The same case also occurred in North Maluku. Historical sources show that the Minang Malay Ulama had a major role in convincing North Maluku Kolano to accept Sharia Islam voluntarily.